Microstructure and strength analysis of dissimilar resistance welds between interstitial free (IF) steel and low carbon steel - Fatemeh Yaghoobi; Roohollah Jamaati; Hamed Jamshidi Aval (Journal of Materials Research and Technology)
Resistance spot welding (RSW) of dissimilar steels, such as interstitial-free (IF) and low-carbon St52 steel, presents challenges due to differences in thermal and electrical properties. This study aims to investigate the effects of welding current and St52 sheet thickness on nugget formation, microstructural evolution, and mechanical performance in St52–IF steel welds. Dissimilar RSW joints were fabricated using varying welding currents (6, 8, and 10 kA) and two St52 thicknesses (0.7 mm and 1 mm), with IF steel fixed at 0.7 mm. Microstructural features were analyzed via optical microscopy, and hardness was measured across the weld zone. Tensile shear tests evaluated joint strength, and fracture modes were examined through macro imaging. Higher welding currents increased nugget size and shifted the weld toward the St52 side due to its higher resistivity. Microstructural transitions from martensite to mixed ferrite-bainite structures were observed with increased heat input. Peak hardness reached 673.3 HV in thick St52 at 6 kA but decreased at higher currents due to slower cooling. Tensile strength improved with current, peaking at 2998.2 N for the 1 mm St52 configuration, while energy absorption declined at 10 kA due to coarse microstructures. Fracture locations depended on sheet thickness and current, shifting from St52 to IF steel as weld quality improved.